2015
DOI: 10.1080/16506073.2015.1016448
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Test of the Additive Benefits of Physical Exercise to CBT for OCD

Abstract: The majority of "responders" to first-line cognitive-behavioural therapy (CBT) and pharmacological treatments for obsessive-compulsive disorder (OCD) are left with residual symptoms that are clinically relevant and disabling. Therefore, there is pressing need for widely accessible efficacious alternative and/or adjunctive treatments for OCD. Accumulating evidence suggests that physical exercise may be one such intervention in the mood and anxiety disorders broadly, although we are aware of only two positive sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…; Rector et al . ; Brellenthin & Koltyn, ). How this occurs remains unclear, although is probably related to the effects of exercise on brain plasticity and metabolism (Johansen‐Berg & Duzel, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Rector et al . ; Brellenthin & Koltyn, ). How this occurs remains unclear, although is probably related to the effects of exercise on brain plasticity and metabolism (Johansen‐Berg & Duzel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Powers, Medina, Burns, Kauffman, Monfils, Asmundson, Diamond, McIntyre, and Smits (this issue) conducted a randomized controlled trial and showed that exposure therapy preceded each week by exercise increased brain-derived neurotrophic factor (BDNF)—a protein shown to play an important role in the extinction of conditioned fear—and reduced PTSD symptoms more than exposure therapy without exercise. In the eighth article, Rector, Richter, Lerman, and Regev (this issue) treated participants with obsessive compulsive disorder (OCD) using group CBT and gym prescribed exercise. They found very large pre- to post-treatment within group effect sizes for the combined intervention on several measures of OCD and other symptoms.…”
mentioning
confidence: 99%
“…These findings were consistent with an earlier work (N=11) conducted by Lancer and colleagues[34] where 6 weeks of brisk walking was associated with significant decreases in OCD symptoms. More recently, Rector and colleagues[21] provided gym memberships and exercise prescriptions to 11 patients with OCD who were beginning CBT treatment for OCD and found significant reductions in OCD symptoms after 12 weeks. While these preliminary studies demonstrated promising findings, each was an uncontrolled pilot study with a small sample.…”
Section: 0 Discussionmentioning
confidence: 99%
“…For example, with the exception of several open pilot trials[1921], there have been no well-controlled, randomized trials of aerobic exercise for symptom reduction in OCD. The purpose of this study was to conduct an RCT of aerobic exercise for patients with OCD who, despite standard treatments, remain clinically symptomatic.…”
Section: 0 Introductionmentioning
confidence: 99%